Pengaruh Edukasi Terhadap Pengetahuan dan Kepatuhan Perawat dalam Discharge Planning di Unit Geriatri RSUD Prof. Dr. Margono Soekarjo dan Paviliun Abiyasa Purwokerto - Anggraeni, Ida; Suroso, Jebul; Etlidawati, Etlidawati; Aprilina, Happy Dwi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Discharge planning is a process that begins from the moment a patient receives healthcare services until they return home. Effective discharge planning can enhance the coordination of services from the hospital to the community, ensure smooth patient discharge, and reduce the length of stay (LOS). However, repeated hospitalizations for the same health issues (readmissions) are still common. Nurses are key members of the discharge planning team and can facilitate the discharge process, helping patients achieve optimal health. Nurses' knowledge and compliance are crucial for the success of discharge planning. To investigate the influence of education on the knowledge and compliance of nurses regarding discharge planning at RSUD (Regional Public Hospital) Prof. Dr. Margono Soekarjo Geriatric Unit and Abiyasa Pavilion Purwokerto. This study employs a pre-experimental design with a one-group pretest-posttest using a paired t-test. The sample consists of 46 respondents who meet the inclusion criteria, selected through simple random sampling. The research instrument is a questionnaire in the form of a Google Form. Univariate analysis uses descriptive analysis, and data normality is tested with the Shapiro-Wilk test. The majority of respondents are female, aged 23-30 years, with the most recent education being a nursing profession degree. The mean knowledge score before education is 44.13 points, and the mean compliance score before education is 5.13 points. After education, the mean knowledge score is 53.78 points, and the mean compliance score is 7.67 points. There is a significant influence on the knowledge and compliance of nurses before and after being given discharge planning education (p-value 0.05), with an average difference in knowledge score of 9.652 points and an average difference in compliance score of 2.543 points. Education has a significant influence on nurses' knowledge and compliance with discharge planning